Shell effects and free-electrons in electromigrated oxidized Cu-nanocontacts. (23rd April 2023) - Hauser, Julia; Rothhardt, Daniel; Pfender-Siedle, Robert; Hoffmann-Vogel, Regina
Abstract: Electromigration in interconnects continues to be an important field of study in integrated circuits as the interconnects are planned to shrink in size at comparable pace as the semiconductor functional elements. Through shrinking the interconnects approach the regime where quantum size effects become important. The observation of quantum size and shell effects is usually restricted either to low-temperatures or vacuum conditions or to chemically inert materials such as Au. Here, we show that in electromigrated Cu nanocontacts such effects can be observed at room temperature and room pressure even in the presence of oxidation. Our data provide evidence that the nanocontacts are nearly spherical objects with a triangular-cylindrical symmetry of their electronic wave functions with a stronger free-electron-like character compared to previous results. We do not observe a detrimental effect of oxygen. The presence of shell effects has implications for the technological use of Cu nanocontacts as interconnects in integrated circuits and could lead to the use of electronic wave functions of shells in such interconnects.